Marine-Derived Furanones Targeting Quorum-Sensing Receptors in : Molecular Insights and Potential Mechanisms of Inhibition - Aaron Boakye; Muntawakilu Padiga Seidu; Alice Adomako; Michael Konney Laryea; Lawrence Sheringham Borquaye (Bioinformatics and Biology Insights, 2024)
The quorum-sensing (QS) machinery in disease-causing microorganisms is critical in developing antibiotic resistance. In Pseudomonas aeruginosa , QS is involved in biofilm formation, virulence factors production, and general tolerance to antimicrobials. Owing to the major role QS plays, interference in the process is probably a facile route to overcome antimicrobial resistance. Some furanone-derived compounds from marine sources have shown promising anti-QS activity. However, their protein targets and potential mechanisms of action have not been explored. To elucidate their potential protein targets in this study, marine metabolites with furanone backbones similar to their cognitive autoinducers (AIs) were screened against various QS receptors (LasR, RhlR, and PqsR) using molecular docking and molecular dynamics (MD) simulation techniques. The order by which the compounds bind to the receptors follows LasR > RhlR > PqsR. Compounds exhibited remarkable stability against LasR and RhlR, likely because the AIs of these receptors are structural analogs of furanones. Furanones with shorter alkyl side chains bound strongly against RhlR. The presence of halogens improved binding against various receptors. PqsR, with its hydrophobic-binding site and structurally different AIs, showed weaker binding. This study provides a molecular basis for the design of potent antagonists against QS receptors using marine-derived furanones.